Effect of launderings on the pilling properties of cotton and polyester weft knitted fabrics / Noraqilah Mohd Azis... [et al.] - Mohd Azis, Noraqilah; Sarani, Siti Farhanim; Nasir, Eryna; Tulos, Najua (Universiti Teknologi MARA, Negeri Sembilan, 2018)
Pilling is one of the fabric faults that originally found in knitted woolen goods especially made from soft twisted yarns. The rubbing action on loose fibres that is present on the fabric surface gives a high tendency to form pills which gives poor appearance to the fabric. This study was carried out to investigate the effect of repeated launderings on the propensity of pilling formation by using pill grade machine. The primary objective of this study was to determine the pilling behaviour of different types of weft knitted fabrics after a repeated number of laundering cycles. The study was conducted using two types of knitted fabrics; cotton and polyester with three types of knitted structures; interlock, 1x1 rib and plain jersey. The various number of laundering cycles were given on the fabrics and followed by 15,000 revolutions of ICI pilling box. The results showed that polyester fibre has better pilling resistance due to its exceptional strength, whilst in terms of fabric structure, plain jersey showed an excellent resistance. This is due to the higher density and compact structure that it possessed.